role of Pleistocene refugia and rivers in shaping gorilla genetic diversity in central Africa - Anthony, Nicola M; Johnson-Bawe, Mireille; Jeffery, Kathryn; Clifford, Stephen L; Abernethy, Kate A; Tutin, Caroline E; Lahm, Sally A; White, Lee J.T; Utley, John F; Wickings, E. Jean; Bruford, Michael W (Proceedings of the National Academy of Sciences - PNAS, 2007)
The role of Pleistocene forest refugia and rivers in the evolutionary diversification of tropical biota has been the subject of considerable debate. A range-wide analysis of gorilla mitochondrial and nuclear variation was used to test the potential role of both refugia and rivers in shaping genetic diversity in current populations. Results reveal strong patterns of regional differentiation that are consistent with refugial hypotheses for central Africa. Four major mitochondrial haplogroups are evident with the greatest divergence between eastern (A, B) and western (C, D) gorillas. Coalescent simulations reject a model of recent east-west separation during the last glacial maximum but are consistent with a divergence time within the Pleistocene. Microsatellite data also support a similar regional pattern of population genetic structure. Signatures of demographic expansion were detected in eastern lowland (B) and Gabon/Congo (D3) mitochondrial haplogroups and are consistent with a history of postglacial expansion from formerly isolated refugia. Although most mitochondrial haplogroups are regionally defined, limited admixture is evident between neighboring haplogroups. Mantel tests reveal a significant isolation-by-distance effect among western lowland gorilla populations. However, mitochondrial genetic distances also correlate with the distance required to circumnavigate intervening rivers, indicating a possible role for rivers in partitioning gorilla genetic diversity. Comparative data are needed to evaluate the importance of both mechanisms of vicariance in other African rainforest taxa.